Ablation and mechanical properties of 3D braided C/ZrC–SiC composites with various SiC/ZrC ratios. Issue 16 (December 2016) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin
Abstract: Three-dimensional (3D) braided C/ZrC–SiC composites with various SiC/ZrC ratios were fabricated by precursor infiltration and pyrolysis (PIP) process. The effects of SiC/ZrC ratios on the ablation and mechanical properties were investigated systematically. The flexural strength of 3D C/ZrC–SiC grows with the increase of SiC/ZrC ratios. The compact and stiff ZrC-SiC matrix, moreover, the carbon fiber and PyC interphase with the less reaction damage account for the improved flexural strength of C/ZrC–SiC with higher SiC/ZrC ratios. As for the ablation properties, both mass and linear ablation rates drop with the decrease of SiC/ZrC ratios at the beginning. However, the ablation rates start to increase with the further decrease of SiC/ZrC ratio, where the high open porosity deteriorates the ablation properties. Herein, in order to obtain a balance between ablation and mechanical properties, an appropriate SiC/ZrC ratio should be considered.